ANALISIS RISIKO ERGONOMI PADA ACCOUNTING UNIT CV. PELANGI REX’S MENGGUNAKAN SNI 9011:2021 - Dewa Ngurah Mahaswara Putera, I Made Dwi Budiana Penindra, Ni Made Cyntia Utami, Anak Agung Istri Ag (Study Program of Industrial Engineering, Udayana University, 2023)
Musculosceletal disorders are the biggest problem for office workers. Ergonomics assessment in the workplace is very important because the potential for health problems in workers can be minimized. SNI 9011:2021 is a method for conducting ergonomics assessments in the workplace and can be used as a national reference in assessing the level of ergonomic risk. The problem was found in the accounting unit workers at CV. Pelangi Rex’s, where the working posture that looks very unergonomic and doesn’t fit the theory of working ergonomically so it needs to be observed further. The purpose of this study was to analyze the level of ergonomic risk in accounting unit workers at CV. Pelangi Rex’s. The sample technique uses a saturated sample technique with a sample count of 8 peoples. Ergonomic risk measurement using SNI 9011:2021. Data analysis using the Spearman Rank test. The results of the statistical test showed that p value = 0,029 and (r) value is 0,76. Result of the study, namely that workers experience pain or pain in almost all limbs, except for the right and left thighs, right and left calves, and right and left legs; potential ergonomic hazards were obtained by as many as 5 workers in the category of need to be further observed and 3 other workers in the hazardous category; and there is a link between potential ergonomic hazards and musculoskeletal complaints and having a strong relationship strength.